Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{3}{x-5}=-\frac{4}{x+2}\)
\(\Leftrightarrow3\left(x+2\right)=-4\left(x-5\right)\)
\(\Leftrightarrow3x+6=-4x+20\)
\(\Leftrightarrow7x=14\)
\(\Leftrightarrow x=2\)
\(\frac{x}{-2}=-\frac{8}{x}\)
\(\Leftrightarrow x^2=16\)
\(\Leftrightarrow x=\pm4\)
\(-\frac{2}{x}=\frac{y}{3}\)
\(\Leftrightarrow xy=-6\)
\(\Leftrightarrow x;y\inƯ\left(-6\right)=\left\{\pm1;\pm2;\pm3;\pm6\right\}\)
Xét bảng
x | 1 | -1 | 2 | -2 | 3 | -3 | 6 | -1 |
y | -6 | 6 | -3 | 3 | -2 | 2 | -1 | 6 |
Vậy.................
\(\frac{2x-9}{240}=\frac{39}{80}\)
\(\Leftrightarrow2x-9=\frac{240.39}{80}\)
\(\Leftrightarrow2x-9=117\)
\(\Leftrightarrow2x=126\)
\(\Leftrightarrow x=63\)
a) 6/2X +1 = 2/7
=6 x 7 = 2(2x+1)
42=4X + 2
42 - 2 = 4X
40 = 4X
10 =X
Câu a là thế này nha \(\frac{-36}{9}\) \(\le\) x \(\le\) \(\frac{-15}{5}\)
1)
\(\frac{7.8^3-5.2^{10}}{\left(-16\right)^2}\)
= \(\frac{7.2^8.2-5.2^8.2^2}{16^2}\)
= \(\frac{2^8.\left(2.7-5.2^2\right)}{2^8}\)
= \(\frac{2^8.\left(-6\right)}{2^8}\)
= \(-6\)
a) 16 - x = 5
x = 16 - 5
x = 11
b ) vì x/ -4 = 18/12
nên 12x = 18 . ( - 4)
=> x = 18 . ( - 4 ) / 12
=> x = -6
c)Ta có : -15/3 = - 15 . 7 / 3 . 7 = -105/21
25/7 = 25 . 3 / 7 . 3 = 75/21
=> - 105/21 <(hoặc = ) x <(hoặc =) 75/21
Làm nốt
d) ( 2x - 8 )(x^ 2 + 3 ) = 0
=> 2x - 8 = 0 ( tm) , x^2 + 3 = 0 ( l)
+) 2x - 8 = 0
2x = 0 + 8
2x = 8
x = 8 : 2
x = 4
#Hoq chắc _ Baccanngon